Long Non-Coding RNA ZSCAN16-AS1 Promotes the Malignant Progression of Melanoma Through Regulating the miR-503-5p/ARL2 Axis - Zhao Y; Zhang X; Wang J; Li Y; Wu Y; Liu J (Dove Medical Press, 2023)
Yuting Zhao,1 Xiangzhou Zhang,1 Jie Wang,2 Yong Li,1 Yitong Wu,1 Jisong Liu1 1Department of Plastic Surgery, the Third the People's Hospital of Bengbu, Bengbu, Anhui, People's Republic of China; 2Department of Plastic Surgery, Affiliated People's Hospital of Jiangsu University, Zhenjiang, Jiangsu, People's Republic of ChinaCorrespondence: Jisong Liu, Department of Plastic Surgery, the Third the People's Hospital of Bengbu, 38 Shengli Road, Bengbu, Anhui, 233099, People's Republic of China, Email 1587827999@qq.comBackground: LncRNA zinc finger and SCAN domain containing 16 antisense RNA 1 (ZSCAN16-AS1), a newly identified lncRNA, has been proven to accelerate hepatocellular carcinoma progression. However, the function and molecular mechanism of ZSCAN16-AS1 in melanoma are still unknown.Methods: The level of ZSCAN16-AS1 in melanoma tissues was detected and reported in The Cancer Genome Atlas (TCGA) and GEO#GSE15605. CCK-8, Transwell and flow cytometry assays were used to explore the role of ZSCAN16-AS1 in melanoma cells. Luciferase reporter assays and RNA pull-down assays were used to verify the molecular mechanism of ZSCAN16-AS1.Results: Here, we found that ZSCAN16-AS1 expression was increased in melanoma. We confirmed that ZSCAN16-AS1 promotes the growth and metastasis of melanoma. ZSCAN16-AS1 exerts its pro-tumour role through sponging of miR-503-5p to liberate ADP-ribosylation factor-like protein 2 (ARL2) mRNA transcripts.Conclusion: These results demonstrated the role and molecular mechanism of ZSCAN16-AS1 in the occurrence and development of melanoma. Therefore, ZSCAN16-AS1 may be used as a specific biomarker in the diagnosis and treatment of melanoma patients.Keywords: melanoma, growth and metastasis, ZSCAN16-AS1, miR-503-5p, ARL2